2012
DOI: 10.1093/eurheartj/ehs376
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1 mutation carriers with low high-density lipoprotein cholesterol are characterized by a larger atherosclerotic burden

Abstract: Carriers of loss of function ABCA1 mutations display a larger atherosclerotic burden compared with age and sex-matched controls, implying a higher risk for CVD. Further studies are needed to elucidate the full function of ABCA1 in the protection against atherosclerosis. These data support the development of strategies to up-regulate ABCA1 in patients with established CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 44 publications
0
43
1
1
Order By: Relevance
“…102 This is supported by a study in ABCA1 heterozygotes in which there was an inverse correlation between cholesterol efflux and carotid atherosclerotic plaque burden as assessed by carotid intima-media thickness. 103 A recent study showed increased atherosclerosis in ABCA1 heterozygotes as assessed by carotid MRI, 101 which is a more specific method for measuring atherosclerotic plaque burden than carotid intimamedia thickness, 104 thus further corroborating the increased atherosclerosis in ABCA1 heterozygotes.…”
Section: Td and Cardiovascular Riskmentioning
confidence: 86%
See 2 more Smart Citations
“…102 This is supported by a study in ABCA1 heterozygotes in which there was an inverse correlation between cholesterol efflux and carotid atherosclerotic plaque burden as assessed by carotid intima-media thickness. 103 A recent study showed increased atherosclerosis in ABCA1 heterozygotes as assessed by carotid MRI, 101 which is a more specific method for measuring atherosclerotic plaque burden than carotid intimamedia thickness, 104 thus further corroborating the increased atherosclerosis in ABCA1 heterozygotes.…”
Section: Td and Cardiovascular Riskmentioning
confidence: 86%
“…107 It must be noted, however, that only small decreases in HDL, of ≈28% as opposed to ≈50% in previously reported ABCA1 heterozygotes, were observed. 94,[101][102][103]107 Also, the residual cholesterol efflux was substantial (74%-79% for P1065S and G1216V and 48%-49% for N1800H and R2144X for homozygous mutations compared with controls), 107 whereas in patients with TD there was only 20% to 30% residual cholesterol efflux. 108 In addition, LDL levels were reduced by ≈25%, probably offsetting the effects of reduced HDL on CVD.…”
Section: Td and Cardiovascular Riskmentioning
confidence: 98%
See 1 more Smart Citation
“…apoA-I has been shown to play a key role in the initial step of reverse cholesterol transport (RCT) ( 7,8 ). Tissue cholesterol effl ux was decreased in patients with the orphan disease of genetically-determined low HDL-c, familial hypoalphalipoproteinemia (FHA) ( 9 ), which coincided with accelerated atherogenesis ( 10,11 ). Early results from infusion experiments with reconstituted HDL corroborated a therapeutic potential, showing increased fecal cholesterol excretion ( 12,13 ), as well as a reduction in the cholesterol content in human atherosclerotic lesions ( 14 ).…”
Section: Plasma Lipids Lipoprotein Profi Les and Apoa-imentioning
confidence: 99%
“…It promotes cellular cholesterol efflux and maintains cellular cholesterol homeostasis [17]. A mutation of ABCA1 has been shown to abolish cholesterol efflux and increase the risk of developing atherosclerosis [18]. ABCA1 is regulated both at the transcriptional level via liver X receptor (LXR)/retinoid X receptor-mediated induction of the ABCA1 gene [19] and at the post-translational level via changes in the turnover of the ABCA1 protein [20].…”
mentioning
confidence: 99%